Crystal structure of 4-[(naphthalen-2-yl)sulfonylamino]methylcyclohexanecarboxylic acid. (March 2015) - Danish, Muhammad; Tahir, Muhammad Nawaz; Hussain, Asif; Ashfaq, Muhammad; Sadiq, Muhammad Nadeem
No abstract available